Antropologia dos Sentidos. Tradução Francisco. Morás. Petrópolis, RJ: Vozes, 2016. - Leitão, Alex Bezerra (Cadernos de Linguagem e Sociedade, 2018)
LE BRETON, D. Antropologia dos Sentidos. Tradução Francisco. Morás. Petrópolis, RJ: Vozes, 2016.